A market segmentation analysis using attitudes towards transport - Gabriela Beirão (2007)
Using attitudes toward travel an exploratory factor analysis was performed followed by a confirmatory factor analysis, showing good validity and reliability indices. Cluster analysis was then used to identify similar respondents based on their travel attitudes. Six distinct groups were extracted: transit enthusiasts, status seekers, car addicts, car-less riders, calm riders and obstinate drivers. The segments showed unique combinations of attitudes with distinct travel behaviors and varying degrees of intention to use public transport. The results show evidence that the design of strategies to influence public transport usage should be targeted at the market segments that are most motivated to change and increase their frequency of use.